2014
DOI: 10.1002/anie.201309532
|View full text |Cite
|
Sign up to set email alerts
|

Axially Chiral Imidodiphosphoric Acid Catalyst for Asymmetric Sulfoxidation Reaction: Insights on Asymmetric Induction

Abstract: Insights into chiral induction for an asymmetric sulfoxidation reaction involving a single oxygen atom transfer are gained through analyzing the stereocontrolling transition states. The fitting of the substrate into the chiral cavity of a new class of imidodiphosphoric Brønsted acids, as well as weak CH⋅⋅⋅π and CH⋅⋅⋅O noncovalent interactions, are identified as responsible for the observed chiral induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…This is presumably because of the more favorable steric arrangement of the reactants (epoxide and thiobenzoic acid tautomers) inside the catalytic cavity as well as the presence of stronger noncovalent interaction in 2b compared to that of 2a. [31][32][33] The catalyst·product complex obtained from TS b (3b; ΔG rel = −19.2 kcal mol −1 ) demonstrates a thermodynamically more stable spacial arrangement inside the chiral cavity than that obtained from TS a (3a; ΔG rel = −16.7 kcal mol −1 ). The pre-transition state ( preTS) complex, 2b, then undergoes a nucleophilic ring opening reaction with simultaneous dual proton transfers assisted by the phosphoric acid group of the catalyst via a concerted asynchronous transition state (eight membered cyclic TS).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is presumably because of the more favorable steric arrangement of the reactants (epoxide and thiobenzoic acid tautomers) inside the catalytic cavity as well as the presence of stronger noncovalent interaction in 2b compared to that of 2a. [31][32][33] The catalyst·product complex obtained from TS b (3b; ΔG rel = −19.2 kcal mol −1 ) demonstrates a thermodynamically more stable spacial arrangement inside the chiral cavity than that obtained from TS a (3a; ΔG rel = −16.7 kcal mol −1 ). The pre-transition state ( preTS) complex, 2b, then undergoes a nucleophilic ring opening reaction with simultaneous dual proton transfers assisted by the phosphoric acid group of the catalyst via a concerted asynchronous transition state (eight membered cyclic TS).…”
Section: Resultsmentioning
confidence: 93%
“…It is interesting to note that the coordination of the thiol form of the acid to 1 results in a termolecular complex 2a (ΔG rel = 7.4 kcal mol −1 ) which has a higher energy than that of the termolecular complex 2b (ΔG rel = −0.2 kcal mol −1 ) resulting from the coordination of its thione tautomer. 31 It was found that non-classical hydrogen bonds such as C-H⋯π and C-H⋯O interactions are important to influence the observed stereoselectivity. The presence of non-classical hydrogen bonds (C-H⋯O interactions) in these prereacting complexes has been verified by Mayer bond order analysis (0.03) and AIM analysis (ρ bcp of the order of 0.02 a.u.).…”
Section: Resultsmentioning
confidence: 99%
“…This is corroborated by quantitative AIM‐based analyses . Thus, overall, the mechanism of this reaction is dictated by the subtle interplay of a number of non‐covalent interactions, which is reminiscent of enzyme‐based catalysis …”
Section: Resultsmentioning
confidence: 99%
“…Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum‐chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, cycloaddition, oxidative addition, isomerization, and many other processes from organic and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%